Dampak Perkembangan Ekonomi Digital Terhadap Perilaku Pengguna Media Sosial dalam Melakukan Transaksi Ekonomi - Nugroho Sumarjiyanto Benedictus Maria; Tri Widayati (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2020)
Indonesia has a great potential influence in the development of the technology world. Technological developments have been in various types of sectors, especially in the development of the digital economy. The digital economy has had positive and negative effects on Indonesia's development. The impact of the development of the digital economy has become a way for the government or the community to be a vehicle for conducting various kinds of economic transactions. For this reason the writing of this article aims to analyze the impact of the development of the digital economy on social media users in conducting economic transactions.